EFFECT OF THERMOTHERAPY IN COMBINATION WITH MER0STEM CULTURE FOR EL0M0NAT0NGPOTATO VIRUS Y (P VY) AND POTATO VIRUS S (P VS) FROM INFECTED SEED STOCKS - S. Y. Ate_; S. nan; M. Ayyaz; .Dündar; D. Yabangülü (Journal of Animal and Plant Sciences, 2019)
The present study was conducted to investigate the impact of thermotherapy along with meristem culture for eliminating Potato virus Y (PVY) and Potato virus S (PVS). The plantlets were subjected to enzyme linked immunosorbent assay (ELISA) to check the presence of targeted viruses. A total of 110 plants including 65 infected with PVY and 45 with PVS belonging to six potato cultivars (Agria, Russet Burbank, Shepody, Granola, Marabel, and Sante) were subjected to thermotherapy (under constant temperature of 36°C and constant light conditions) for a period of five weeks. The obtained results revealed no PVY and PVS positive plants after five week of thermotherapy. However, plant mortality was observed in cv. Granola, R. Burbank, Shepody and Agria. Cv. Granola was sensitive, whereas, Sante and Marabel were found to be resistant cultivars. Marabel and Sante responded effectively to thermotherapy treatment by producing PVY and PVS negative plants with no plant mortality after application of thermotherapy. The study showed that propagation of clean production material is possible by applying thermotherapy treatment along with tissue culture method by using meristem culture and shoot tips cultures.
Keywords: Potato; thermotherapy; PVY; PVS; DAS-ELISA; Meristem culture